Conditioned Taste Aversion : Neural and Behavioral Processes. - Reilly, Steve (Oxford University Press, USA, 2008)
Conditioned taste aversion is arguably the most important learning process that humans and animals possess because it prevents the repeated self-administration of toxic food. It has not only profoundly influenced the content and direction of learning theory, but also has important human nutritional and clinical significance. In addition to its direct relevance to food selection, dietary habits, and eating disorders, it is significant for certain clinical populations that develop it as a consequence of their treatment. The study of conditioned taste aversions has invigorated new theory and rese.